Microemulsions for enhancing drug delivery of hydrophilic drugs: Exploring various routes of administration - Khushwant S. Yadav; Govind Soni; Deepak Choudhary; Arushee Khanduri; Ayush Bhandari; Garima Joshi (Medicine in Drug Discovery, 2023)
Microemulsions are a promising drug delivery system that can be used to enhance the bioavailability, solubility, and therapeutic efficacy of hydrophilic drugs. The downside of hydrophilic drugs is the poor solubility in lipid-based media; therefore, they require frequent dosing or high doses to achieve the therapeutic level. This may lead to unintended adverse effects and poor patient compliance Microemulsions can improve drug delivery by incorporating hydrophilic drugs within a thermodynamically stable and transparent oil-in-water emulsion. This can optimize the drug's solubility and permeability, leading to enhanced bioavailability and therapeutic efficacy. This review provides an insight to various routes of administration for delivering hydrophilic drugs using microemulsion. It will explore the use of microemulsion for oral, nasal, transdermal, and ocular delivery. The review also discusses the advantages, disadvantages and the physicochemical properties associated with each one of it. Overall, the article aims to provide a comprehensive overview of the use of microemulsions as a drug delivery system for hydrophilic drugs administered via different routes.